2013
DOI: 10.1093/scan/nst071
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in event-related potentials for early visual processing of emotional faces

Abstract: With advancing age, processing resources are shifted away from negative emotional stimuli and toward positive ones. Here, we explored this 'positivity effect' using event-related potentials (ERPs). Participants identified the presence or absence of a visual probe that appeared over photographs of emotional faces. The ERPs elicited by the onsets of angry, sad, happy and neutral faces were recorded. We examined the frontocentral emotional positivity (FcEP), which is defined as a positive deflection in the wavefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
5
21
1
Order By: Relevance
“…While young adults recall negative events more easily than neutral events (Negativity bias; [90], older people tend to mainly focus on positive stimuli [91] and the ability to recognize negative facial expressions declines [92][93][94]. This may depend on early automatic and implicit processes of attentional avoidance [95], rather than higher level of cognitive elaboration of the stimulus content [96]. In older adults, this kind of "optimism" is also related to anxiety [97,98], particularly in the perception of emotional threatening faces [91,99].…”
Section: The Visual Discrimination Of Emotion In MCImentioning
confidence: 99%
“…While young adults recall negative events more easily than neutral events (Negativity bias; [90], older people tend to mainly focus on positive stimuli [91] and the ability to recognize negative facial expressions declines [92][93][94]. This may depend on early automatic and implicit processes of attentional avoidance [95], rather than higher level of cognitive elaboration of the stimulus content [96]. In older adults, this kind of "optimism" is also related to anxiety [97,98], particularly in the perception of emotional threatening faces [91,99].…”
Section: The Visual Discrimination Of Emotion In MCImentioning
confidence: 99%
“…In a combined functional magnetic resonance imaging (fMRI) and event-related potentials (ERP) study by Williams and colleagues [ 7 ], no significant age-related changes in the temporooccipital components emerged, suggesting preservation of emotional facial encoding across lifespan. Using a go/no go task with positive, negative, and neutral facial expressions (task irrelevant stimulation), Hilimire et al [ 8 ] found pronounced early negativity at occipital sites and positivity at frontocentral sites to positive emotions in older adults. In young adults, a similar pattern emerged for negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…In young adults, a similar pattern emerged for negative emotions. The authors concluded that aging is characterized by enhanced early processing of positive emotions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…At this level, previous research has reported early orientation of attention to low-level facial characteristics (black versus white faces; e.g., Ito & Urland, 2003). Similarly, it has been suggested that these potentials reflect a fast global extraction of salient emotional information before fine-grained face decoding (e.g., Dennis, Malone, & Chen, 2009;Eimer & Holmes, 2002;Hilimire et al, 2014;Pitcher, Walsh, Yovel, & Duchaine, 2007;Pizzagalli et al, 2002;Pourtois, Dan, Grandjean, Sander, & Vuilleumier, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…The earliest ERP responses to face stimuli appear approximately one hundred milliseconds after stimulus onset at the posterior bilateral P1 and the central N1 (Eimer & Holmes, 2002;Hilimire, Mienaltowski, Blanchard-Fields, & Corballis, 2014;Yang, Gu, Guo, & Qiu, 2011). At this level, previous research has reported early orientation of attention to low-level facial characteristics (black versus white faces; e.g., Ito & Urland, 2003).…”
Section: Introductionmentioning
confidence: 99%